Mexico : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper analyzes reforms to Mexico's fiscal framework. Mexico's resilient economic performance would be consolidated by increasing fiscal policy buffers and preparing for challenges associated with long-term budget pressures. In the short term, reducing public debt levels can create space to implement countercyclical fiscal policies and reduce exposure to high financing and hedging costs, which would protect Mexico's credit rating at times of distress. The paper highlights that recent fiscal reform is designed with these policy objectives in mind, to build on the strengths of the previous fiscal framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet